(3GdJPcQGJ hJQHjI GdeDefs
(3ChdgG (B:s
(3gPg aUhd ef GdehGYX cd aUd efgG jMdj eLdS GdehGYX hjTJed Ydi GdJhHjN hGdedGe adjcf ai BNQ GdcdGe s
(3BNQgG (B:s
(3hGUdM cd bdH efG hCdMbfG HGdeJbjf hCdHSfG NdY GdEjeGf hGdjbjf hGdMeO ddg QH GdYGdejf hGdUdhGJ Ydi QShd SjOfG eMeO hBdg CLeYjf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(D 321) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs